Analysis of Speech Acts During Speaking Classes at SMP PGRI 5 Denpasar - Subagiasih, N.L.E. (Universitas Pendidikan Ganesha, 2018)
This study aimed at and analyzing the types of speech act and the functions of speech act during EFL learning in SMP PGRI 5 Denpasar. The study was designed in the form of descriptive qualitative study which involved an English teacher and eight grade students at SMP PGRI 5 Denpasar. The theory of Searle (1979) was used as the grand theory for analyzing the speech act types and Leech’s (1991) was used for the analyzing the function of the speech act. The data were obtained through observing, recording and note taking. The instrument used in this study were researcher (the main instrument), observation sheet, and video recording (the additional ones). The data were analyzed descriptively. The types of speech acts used in EFL learning were directives, representatives, commisisves, expressives, and declaratives category. In EFL learning mostly created speech acts for the competitive, collaborative, convivial, and conflictive function.